2017
DOI: 10.1038/s41598-017-13117-5
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Red Light-Emitting Diode treatment in experimental model of acute lung injury induced by sepsis

Abstract: Sepsis is a severe disease with a high mortality index and it is responsible for the development of acute lung injury (ALI). We evaluated the effects of light-emitting diode (LED) on ALI induced by sepsis. Balb-c mice were injected with lipopolysaccharide or saline and then irradiated or not with red LED on their tracheas and lungs for 150 s, 2 and 6 h after LPS injections. The parameters were investigated 24 h after the LPS injections. Red LED treatment reduced neutrophil influx and the levels of interleukins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Siqueira and coauthors [24] also observed that red LED (660 nm) decreased the lung inflammatory infiltration in an experimental model of asthma. In addition, in earlier studies of our group using phototherapy in lung inflammation model induced by CLP we showed similar effects of phototherapy in the reduction of inflammatory cells of the lung [26]. It may be suggested that the energy offered to the lung tissue was able of inducing an appropriate tissue-response, modulating the inflammatory process.…”
Section: Discussionsupporting
confidence: 68%
“…Siqueira and coauthors [24] also observed that red LED (660 nm) decreased the lung inflammatory infiltration in an experimental model of asthma. In addition, in earlier studies of our group using phototherapy in lung inflammation model induced by CLP we showed similar effects of phototherapy in the reduction of inflammatory cells of the lung [26]. It may be suggested that the energy offered to the lung tissue was able of inducing an appropriate tissue-response, modulating the inflammatory process.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, a recent case report suggested the therapeutic potential of phototherapy with a red light (630 + 660 nm) for the alleviation of respiratory symptoms, pulmonary inflammation, and hypoxia [103]. The beneficial effect of red light (660 nm) was also confirmed in an experimental model of sepsis-associated ALI [104]. Although most peripheral tissues, except the eye and skin, are not normally reached by light, accumulating evidence suggests the direct and indirect impacts of visible light on cell behavior and biological activities through opsin (OPN) receptors [105].…”
Section: Discussionmentioning
confidence: 90%
“…Although the in vivo photothermal treatment was not performed due to limitations of our biosafety level 3 facilities and the availability of an appropriate light source, the in vitro experiments suggest it may further improve the therapeutic effect of the multifunctional NPs, which is also supported by previous studies. It has been reported that phototherapy can treat lung inflammation [ 84 ] and lung injury [ 85 ] in vivo after red light irradiation on the respiratory tract. In vivo ablation of lung cancer [ 86 ] and other different types of cancers including skin cancer, [ 87 ] breast cancer, [ 88 ] glioblastoma, [ 66 ] mammary cancer, [ 89 ] and colorectal cancer [ 90 ] were achieved by photothermal therapies using red/near‐infrared light excitation.…”
Section: Resultsmentioning
confidence: 99%